Public Relations Strategy of PT KAI Daop 1 Jakarta in Enhancing Brand Awareness through Instagram Content @mashumas_ - Dinda Nur Syafitri; Wahyu Budi Priatna (Communica : Journal of Communication, 2026)
The rapid development of digital technology has encouraged public relations practitioners to utilize social media strategically to build brand awareness. However, studies on brand awareness in government related corporate institutions through Instagram based public relations remain limited. This study analyzes the public relations strategy implemented by PT KAI Daop 1 Jakarta through the Instagram account @mashumas_ to enhance brand awareness. Unlike previous studies focusing on customer service communication, corporate image, or general social media strategies, this research examines brand awareness through a newly established Instagram account by integrating Excellence Theory and the Four-Step Public Relations Model to analyze content strategy and two-way communication practices. This study employed a qualitative descriptive case study approach. Data were collected through in-depth interviews with four informants, including the Public Relations Manager, two PR staff members, and an internship student at PT KAI Daop 1 Jakarta. Documentation of Instagram feeds, reels, and stories was also analyzed. Data were analyzed using the interactive model of Miles et al., with source triangulation applied to ensure validity. The findings reveal that collaborative content planning, trend adaptation, and the integration of informative and entertaining content effectively increased audience engagement. Interactive reels and posts generated higher views, comments, shares, and follower growth, while two-way communication strengthened public recognition of PT KAI Daop 1 Jakarta and its activities. Strategic Instagram content management supports brand awareness by encouraging audience engagement through interactive and adaptive communication. The findings demonstrate the importance of integrating strategic planning, trend adaptation, and continuous evaluation in digital public relations practices within government-related corporate institutions.